Interface-engineered CuBi2O4/biomass-derived activated carbon composites for supercapacitors - J. Venkatesan; J. Preethi Rency Fathima; J. Bosco Franklin; A. Padmanaban; A. Kumaresan; S. John Sundaram; P. Maadeswaran; Kasinathan Kaviyarasu (Biomass and Bioenergy, 2026)

Floral Phenology and Changes in Economic Traits During Different Stages of Fruit Growth and Development in Seven Avocado Accessions - Vittal Kamble; Narayana C.K.; Sudhakar Rao D.V.; Karunakaran G.; Sangeetha Priya S.; Vijay Rakesh Reddy S.; Preethi P. (Applied Fruit Science, 2026)

The Structural and Luminescent Features of Strontium Alumino Borosilicate Glass with CuO for Optical Device Applications - V. Uma Lakshmi; N. Preethi; Bakr Mahmood Hussein; K. S. Rudramamba; M. Rami Reddy (Journal of Fluorescence, 2026)

Statistical simulation of extreme storm events and wave climates off the Puducherry coast, western Bay of Bengal - R. Mahesh; G.M. Mridula; S.K. Raju; S. Preethi; V. Ramanathan; M.V. Ramana Murthy; R.S. Kankara (Ocean Engineering, 2026)

A stochastic multivariate extreme-value model for storm and wave climate off the west coast of India - R. Mahesh; S. Preethi; S.K. Raju; J. Satheesh Kumar; V. Ramanathan; M.V. Ramana Murthy; R.S. Kankara (Ocean Engineering, 2026)

Computational screening of lichen bioactive compounds as a potential antiviral agent against SARS-CoV-2 main proteases - S. Jeya Preethi; A. Yamuna; M. Arunkumar; E. Murugesh; P. Ponmurugan; P. Shanmughavel (In Silico Pharmacology, 2026)

Improved two stage triangular fuzzy STARMA model for drought forecasting in Southern Telangana - Ch. Preethi; A. Meena; Santosha Rathod; Balaji Naik B; S. Vishnu Shankar; Amit Saha; Mrinmoy Ray; Rahul Patil (Journal of Hydrology, 2026)

Synergistic Effects of Ethylene Inhibitors and Cold Storage on the Postharvest Quality of Papaya Fruits - Pavankumar M; Sudhakar Rao D. V.; Vijay Rakesh Reddy Sanikommu; Preethi P.; Vasugi C.; Shivasankara K. S.; Sriram S. (Applied Fruit Science, 2026)

Isolation and characterization of Xanthomonas campestris pv. campestris from cabbage and its Inhibition using endophytic bacteria - S. Preethi; S. Umesha (Vegetos, 2025)

Facile synthesis of zinc ferrite magnetic nanoparticles for antibacterial application - Savari Muthu Sachin; G. Govindasamy; S. John Sundaram; J. Preethi Rency Fathima; M. Sherlin Nivetha (Nanotechnology for Environmental Engineering, 2025)

Comprehensive insights into black rot of crucifers: pathogen–host dynamics and sustainable control methods - S. Preethi; S. Umesha (Journal of Plant Diseases and Protection, 2025)

Piper betle extract inhibits ferroptosis by scavenging oxyradicals, hydroperoxides and inducing NRF2 regulated antioxidants - Veena Ranganathan; Vidyaranyapura S. Deepashree; Jadeppa Gowda; Sumit K. Dey; Souparnika H. Manjunath; Preethi G. Anantharaju; Durgesh Paresh Bidye; Gurubasavaraj V. Pujar; Vinesh J. Maharaj; Rajesh K. Thimmulappa (Food Bioscience, 2025)

Retraction notice to “Advances in bioremediation of emerging contaminants from industrial wastewater by oxidoreductase enzymes” [Bioresour. Technol. 359 (2022) 127444] - P.Sai Preethi; N.M. Hariharan; Sundaram Vickram; M. Rameshpathy; S. Manikandan; R. Subbaiya; N. Karmegam; Vivek Yadav; Balasubramani Ravindran; S.W. Chang; Mukesh Kumar Awasthi (Bioresource Technology, 2025)

Exploring Withanolides from Withania somnifera: A Promising Avenue for Alzheimer’s Disease Treatment - Chitikela P Pullaiah; Preethi Priyadharshini SP; Phareedha SK; Yamini Nemalapalli; Geetha Birudala; S Lahari; Shanmugam Vippamakula; R Shakila; Muni Swamy Ganjayi; Raghavendra Mitta (Current Pharmacology Reports, 2025)

Rice night-time thirst: Genotype nutrient needs reflected in nocturnal transpiration - Spoorthi Nagaraju; Mohan Ramesh; Noor E Mujjassim; Sandeep Reddy A S; Preethi Vijayaraghavareddy; Sheshshayee Sreeman (Rhizosphere, 2024)

Microwave facilitated bacterial liquefaction of sago biomass for efficient biomethane production: Energy and cost assessment - Sudharsh S; Preethi; Rashmi Gondi; Insuvai S; Chitrali Laha Roy; Yukesh Kannah R; Gunasekaran M; Pugalenthi V; Meganathan Kannan; Rajesh Banu J (Process Safety and Environmental Protection, 2024)

Exploring the Potential of Nickel Oxide Nanoparticles Synthesized from Dictyota bartayresiana and its Biological Applications - G. V. Geethamala; A. V. Swathilakshmi; S. Keerthana; D. Vidhyanivetha; G. Preethi; P. Chitra; M. Poonkothai (Biological Trace Element Research, 2024)

Waves of change: Electrochemical innovations for environmental management and resource recovery from water – A review - S. Manikandan; S.R. Deena; R. Subbaiya; D.S. Vijayan; Sundaram Vickram; B. Preethi; N. Karmegam (Journal of Environmental Management, 2024)

Computing the Quality Characters and Acceptability of Convective Air Dried Germinated Cashew Seed Powders - P. Preethi; S. Mangalassery; S. V. R. Reddy; T. Harish; G. L. Veena; R. Pandiselvam (Applied Fruit Science, 2024)

Effect of bacterial pretreatment on solid sago waste for enhanced biomethane generation - S. Sudharsh; V. Lavanya; Preethi; Rashmi Gondi; Chitrali Laha Roy; Meganathan Kannan; J. Rajesh Banu (Bioresource Technology Reports, 2024)

Highly Efficacious Oil–Water Separation by Facile Stacking of the Iron Powder Waste - V. Preethi; S. T. Ramesh; R. Gandhimathi (Water, Air, & Soil Pollution, 2024)

Differential Efficacy of Postharvest Application of Ethylene Inhibitors on Storage Life and Nutritional Quality of Guava (cv. ‘Arka Mridula’) - A. J. Sachin; D. V. Sudhakar Rao; K. Ranjitha; C. Vasugi; C. K. Narayana; S. Vijay Rakesh Reddy; P. Preethi (Applied Fruit Science, 2024)

Analysis of localized features during wet and dry rainfall episodes over southern tip of India - E. A. Resmi; B. Preethi; R. S. Ajayamohan; Pallav Ray; C. K. Unnikrishnan; S. Nita; R. K. Sumesh; J. Dharmadas (International Journal of Climatology, 2023)
The large spatial and temporal variability of wet and dry spells of the Indian Summer Monsoon (ISM) poses the great challenge in understanding and predicting monsoonal rainfall. This challenge is further exacerbated over smaller regions, such as the southern tip of India, which receives the first spell of ISM rainfall. In this study, the characteristic features and possible precursors for wet and dry spells of rainfall over the southern tip of India are investigated. We also explore the variability in monsoon low‐level jet (LLJ) in relation to wet and dry spells over a coastal station Thiruvananthapuram (8.48°N, 76.95°E) in southwest India using in situ observations and other ancillary datasets. The results show that a wet spell spanning 3–4 days contributes about 30% of seasonal rainfall. Wet spells are characterized by westerly wind anomaly in the southern tip of India and easterly wind anomaly in northern India, leading to anomalous cyclonic vorticity over the Indian subcontinent. The opposite happens during dry spells. These characteristics are prominent from 2 days prior to the initiation of the spells, suggesting they may be used as precursors for forecasting wet and dry spells over Thiruvananthapuram. Analysis of low‐ to mid‐tropospheric (2 and 4 km) humidity reveals significant moistening (drying) during wet (dry) spells. Yet, both wet and dry spells experience humid (>80%) boundary layer. The differences in mid‐level humidity and thermodynamical structures between wet and dry spells seem to contribute to distinct rainfall characteristics over the southern tip of India. These results indicate that the use of in situ observations along with large‐scale reanalysis datasets may provide valuable information on the precursors for wet and dry spells over the southern tip of India, which can help both in regional‐ and city‐level planning and management of water resources.

Correction to: The Effects of Long-term, Low-dose β-N-methylamino-L-alanine (BMAA) Exposures in Adult SODG93R Transgenic Zebrafish - Ryan D. Weeks; Sandra A. Banack; Shaunacee Howell; Preethi Thunga; James S. Metcalf; Adrian J. Green; Paul A. Cox; Antonio Planchart (Neurotoxicity Research, 2023)

The Effects of Long-term, Low-dose β-N-methylamino-l-alanine (BMAA) Exposures in Adult SODG93R Transgenic Zebrafish - Ryan D. Weeks; Sandra A. Banack; Shaunacee Howell; Preethi Thunga; James S. Metcalf; Adrian J. Green; Paul A. Cox; Antonio Planchart (Neurotoxicity Research, 2023)

Relevance of acquired tolerance traits and root length in determining spikelet fertility and yield in rice - V. S. Lekshmy; Preethi Vijayaraghavareddy; Karthik S. Nanaiah; Sheshshayee Sreeman (Plant Physiology Reports, 2022)

Research on sustainable development for environmental management - Soundara Balu; Mangottiri Vasudevan; Rakesh J. Pillai; S. Bhuvaneshwari; V. Preethi; V. Jeevanantham (Environmental Science and Pollution Research, 2022)

Synthesis of silver nanoparticles from Indian red yeast rice and its inhibition of biofilm in copper metal in cooling water environment - Muthukumar Suganya; Parameswaran Sujatha Preethi; Jayaraman Narenkumar; Arumugam Arul Prakash; Sandhanasamy Devanesan; Mohamad S. AlSalhi; Aruliah Rajasekar; Ayyakkannu Usha Raja Nanthini (Environmental Science and Pollution Research, 2022)

Review on NAD(P)H dehydrogenase quinone 1 (NQO1) pathway - S. Preethi; K. Arthiga; Amit B. Patil; Asha Spandana; Vikas Jain (Molecular Biology Reports, 2022)

Protective Effects of Sauropus Androgynus Leaf Extract against Isoproterenol Induced Cardiotoxicity - Preethi S.; Hitesh Kumar; Ramesh C.; Sowmya B. A.; Niveditha K.; Ramkishan Ajmeer; Vikas Jain (Cardiovascular Toxicology, 2022)

Spatial assessment of Groundwater Quantity and Quality: A case study in parts of Chidambaram Taluk, Cuddalore District, Tamil Nadu, India - S. Venkatesan; S. Arumugam; M. Bagyaraj; T. Preethi; P. Parthasarathy (Sustainable Water Resources Management, 2021)

Role of physical oceanography parameters in ocean’s biological response with the passage of cyclone Titli in the Bay of Bengal - K Vijay Prakash; Ch S Geetha Vimala; P V Nagamani; N K Baranval; Shivashankar Manche; T Preethi Latha; I V G Bhavani; Y Umamaheswara Rao; Ch S N Phanindra; K Srinivas; K P Kumari (Journal of Earth System Science, 2021)

Assessment of Water Quality Along the Southeast Coast of India During COVID-19 Lockdown - K. Vijay Prakash; Ch. S. Geetha Vimala; T. Preethi Latha; Chiranjivi Jayaram; P. V. Nagamani; Ch. N. V. Laxmi (Frontiers in Marine Science, 2021)
The COVID-19 pandemic has affected the entire world and has had a devastating impact on both lives and livelihoods in India. The only way to defeat the rapid spread of COVID-19, is to shut down socio-economic activities and to maintain minimal human interaction with the implementation of a lockdown. Such lockdowns have manifested in a pollution curtailment in almost all spheres of the planet, including in marine pollution. Quantifying this decrease in pollution levels enables the scientific community to assess the contribution of anthropogenic (especially non-essential) activities to global/regional pollution levels. This paper aims to study the impact of the stringent lockdown period (phase 1 and 2) on coastal water quality along the Chennai coast of India, by analyzing suspended matter concentration (SPM), a key element of water quality and diffuse attenuation coefficient, K d (490), using LANDSAT-8 Operational Land Imager (OLI) data. LANDSAT-8/OLI, L1TP scenes were subjected to radiometric calibration and atmospheric correction to derive surface reflectance values from raw digital numbers using ACOLITE software and a brief insight has been given for the Dark Spectrum Fitting algorithm used in ACOLITE. SPM concentration decreased by 15.48 and 37.50% in the Chennai and Ennore ports, respectively, due to minimal vessel movement and cargo handling. The stringent lockdown led to the operation of fewer thermal plant units, thus less fly ash was emanated, resulting in a 28.05% reduction in SPM levels over Ennore creek. As industrial and commercial activities subsided, the city’s water bodies became clearer than they were just a fortnight prior to the lockdown, with a reduction of 22.26% of SPM in Adyar and 33.97% in Cooum riverine estuaries. Decrease in K d (490) showed a positive relationship with SPM and thus improved coastal water quality because of the reduction of SPM during this period. The variations in PM2.5 and PM10 concentrations were studied using National Air Quality Monitoring Programme (NAMP) data and reduced levels in particulate matter concentration (PM2.5 and PM10) for the Adyar residential area (24.38 and 28.43%) and for the Nungampakkam commercial area (36.09 and 67.18%) were observed. A significant reduction in PM2.5 concentration (45.63%) was observed in the Ennore-Manali Industrial region.

Development of EST-SSR markers for genetic diversity analysis in coconut (Cocos nucifera L.) - P. Preethi; Shafeeq Rahman; S. Naganeeswaran; A. A. Sabana; K. P. Gangaraj; B. A. Jerard; V. Niral; M. K. Rajesh (Molecular Biology Reports, 2020)

Leaf blast disease in finger millet [Eleusine coracana (L.) Gaertn.] caused by Bipolaris sorokiniana Sacc.: a histopathological study - Pereira Preethi; M. S. Sharada; C. R. Divya (Journal of Plant Diseases and Protection, 2020)

Dietary amaranths modulate the immune response via balancing Th1/Th2 and Th17/Treg response in collagen-induced arthritis - Jasmine Peter; Vidya Sabu; I. S. Aswathy; Santhi Krishnan; S. S. Lal Preethi; Monisha Simon; A. Helen (Molecular and Cellular Biochemistry, 2020)

Variability of Indian summer monsoon droughts in CMIP5 climate models - B. Preethi; R. Ramya; S. K. Patwardhan; M. Mujumdar; R. H. Kripalani (Climate Dynamics, 2019)

Eco-concrete for sustainability: utilizing aluminium dross and iron slag as partial replacement materials - Shriraksha Javali; A. R. Chandrashekar; Sujay Raghavendra Naganna; D. S. Manu; Parameshwar Hiremath; H. G. Preethi; N. Vinod Kumar (Clean Technologies and Environmental Policy, 2017)

Comprehensive strategy for the design of precision drugs and identification of genetic signature behind proneness of the disease—a pharmacogenomic approach - Preethi M Iyer; S Karthikeyan; P Sanjay Kumar; P K Krishnan Namboori (Functional & Integrative Genomics, 2017)

Cyclosporine A-Mediated IL-6 Expression Promotes Neural Induction in Pluripotent Stem Cells - Ashwathnarayan Ashwini; Sushma S Naganur; Bhaskar Smitha; Preethi Sheshadri; Jyothi Prasanna; Anujith Kumar (Molecular Neurobiology, 2017)

Satellite and In Situ Observations of a Phytoplankton Bloom from Coastal Bay of Bengal: Role in pCO2 Modulation - Rajdeep Roy; K. H. Rao; T. Preethi Latha; Vinay Kumar Dadhwal; V. V. S. S. Sarma; P. V. Nagamani; S. B. Choudhury; Seetharam Pondala (Journal of the Indian Society of Remote Sensing, 2017)

Estimation of Air-Sea CO2 Flux in the Coastal Waters of Visakhapatnam - T. Preethi Latha; K. H. Rao; V. V. S. S. Sarma; P. Seetaram; S. B. Choudhury; P. V. Nagamani; C. B. S. Dutt; V. K. Dhadwal; Sudip Manna (Journal of the Indian Society of Remote Sensing, 2015)

Setting of Cloud Albedo in the Atmospheric Correction Procedure to Generate the Ocean Colour Data Products from OCM-2 - P. V. Nagamani; T. Preethi Latha; K. H. Rao; T. Suresh; S. B. Choudhury; C. B. S. Dutt; V. K. Dadhwal (Journal of the Indian Society of Remote Sensing, 2015)

Retrieval and Validation of Chlorophyll-a Concentrations in the Coastal Waters Off Yanam and Kakinada (Godavari) Basin Along East Coast of India - T. Preethi Latha; P. V. Nagamani; K. H. Rao; S. K. Dash; S. B. Choudhury; Aziz Rehman; V. V. S. S. Sarma; M. Naveen Babu; P. Amarendra; B. Srinivasa Rao; T. D. V. Prasad (Journal of the Indian Society of Remote Sensing, 2014)

Degradation of Untreated Switchgrass Biomass into Reducing Sugars in 1-(Alkylsulfonic)-3-Methylimidazolium Brönsted Acidic Ionic Liquid Medium Under Mild Conditions - Ananda S. Amarasekara; Preethi Shanbhag (BioEnergy Research, 2013)

Seasonal behaviour of NCEP-NCAR longwave cloud radiative forcing and its relationship with all-India summer monsoon rainfall - A. A. Munot; S. D. Patil; B. Preethi; N. Singh (International Journal of Remote Sensing, 2011)

Biotransformation of Meloxicam by Cunninghamella blakesleeana: Significance of Carbon and Nitrogen Source - Gurram Shyam Prasad; Kollu Narasimha Rao; Rama Preethi; Sivasri Girisham; S. M. Reddy (Indian Journal of Microbiology, 2011)